In Vitro Development and Mitochondrial Gene Expression in Brown Brocket Deer (Mazama gouazoubira) Embryos Obtained by Interspecific Somatic Cell Nuclear Transfer - Magalhães, Lívia C.; Cortez, Jenin V.; Bhat, Maajid H.; Sampaio, Ana Clara N.P.C.; Freitas, Jeferson L.S.; Duarte, José M.B. [UNESP]; Melo, Luciana M.; Freitas, Vicente J.F. (SAGE Publications, 2020)
The genetic diversity of Neotropical deer is increasingly jeopardized, owing to declining population size. Thus, the formation of cryobanking of somatic cells is important for the preservation of these species using cloning. The transformation of these cells into viable embryos has been hampered by a lack of endangered species oocytes. Accordingly, the aim of this study was to produce brown brocket deer embryos by interspecific somatic cell nuclear transfer (iSCNT), using goat or cattle oocytes as cytoplasts, and to elucidate embryo mitochondrial activity by measuring the expression levels of ATP6, COX3, and ND5. Cattle embryos produced by in vitro fertilization (IVF) were used as a control. There were no differences in the development of embryos produced by traditional SCNT and iSCNT when using either the goat cytoplasts (38.4% vs. 25.0% cleaved and 40.0% vs. 50.0% morula rates, respectively) or cattle cytoplast (72.8% vs. 65.5% cleaved and 11.3% vs. 5.9% blastocyst rates, respectively). Concerning the gene expression, no significant difference was observed when goat oocytes were used as cytoplasts. However, when using cattle oocytes and 16S as a reference gene, the iSCNT upregulated COX3, when compared with SCNT group. In contrast, when GAPDH was used as a reference gene, all the evaluated genes were upregulated in the iSCNT group, when compared with the IVF group. When compared with the SCNT group, only the expression of ATP6 was statistically different. In conclusion, it was demonstrated that interspecific nuclear transfer is a potentially useful tool for conservation programs of endangered similar deer species.
Keywords: cloning; conservation; deer; gene expression; mitochondria; nuclear transfer